Editorial - Robles Olivos, Rafael Alexis (2021)
The pandemic caused by COVID-19, added to the proliferation of fake news on the Internet, reinforces the importance of the scientific study of communications for an adequate system of production, dissemination and consumption of information for the understanding of social agents.